The Relationship Between Some Kinematical Variables and Visual accuracy of Low Forehand Jump Setting in Volleyball Setters - Yasir, Alaa; Hussain, Mustafq (Journal of Physical Education, 2022)
The research aimed at identifying the relationship between some kinematical variables and in low forehand jump setting in volleyball setters. The subjects were (5) volleyball setters from Al Jaish and Al Senaa setters. The researchers used the descriptive method with iPhone camera 120 pix/sc. The data was collected and treated using SPSS to conclude significant correlation relationship between kinematical variables and vision accuracy of setters.